An attempt to improve air quality in primary schools - Telejko, Marek; Zender-Świercz, Ewa (International Conference “Environmental Engineering”, 2017)
Most primary school buildings in Poland rely on natural ventilation. This fact is attributed to the age of these buildings constructed more than dozen or even several tens of years ago. Few of them were fitted with a mechanical ventilation system allowing for the adjustment of microclimate parameters. The national requirements for gravity ventilation provide general guidelines, specifying strict description only for the airtightness of windows and doors and the minimum airflow to be supplied to the rooms. The minimum airflow supplied is independent of the number of occupants and purpose of the room. Low indoor air quality (IAQ) can impact occupants’ health and lead to poor productivity or low academic performance. Therefore the provision of good IAQ in classrooms and laboratories is very important. This paper presents the results of the investigation devoted to the quality of indoor air in classrooms of selected Polish primary school. Six primary school in a town with a population of 200 000 inhabitants were involved in the investigations. The participating school buildings were built between 1976 and 1994 and had gravity ventilation systems. The variability of basic IAQ parameters, i.e., temperature, relative humidity and carbon dioxide level, was analysed and the assessment of the classrooms in terms of microbiological purity was performed. The outcomes confirmed the low quality of the indoor air in these buildings. The maximum value of CO2 concentration amounted to more than 4000 ppm. Certain modifications aimed at improving IAQ were proposed during the investigations. Two solutions were implemented. The results of this study indicate that the proposed solution offers the potential to improve IAQ within classrooms.